Redefining school safety and policing: a transformative four-pillar model - Yarbrough, Jeffrey D. (Routledge, Taylor & Francis, 2024)
"Redefining School Safety and Policing identifies and works to eliminate systemic issues in school policing that negatively impact students of color, LGBTQIA+ students, and other marginalized populations. Focusing on the fundamental goal of creating safe learning environments, Yarbrough lays out the unintended consequences of involving police in the administrative disciplinary process, as agents of school administrators and enforcers of zero-tolerance policies. Behavioral health support is important to students going through social, emotional, and mental health crises. True equity work brings everyone to a safe space in the middle, encouraging open discussion and courageous dialogue and aiming to create positive change. Yarbrough argues that behavioral health and racial equity are vital to transforming school policing and providing beneficial alternative solutions to school policing that do not lead students to the juvenile or criminal justice system. This book is suitable for school administrators, teachers, counselors, social workers, police and school resource officers, and community activists working to defund the police"--